Bioremediation of toxic metals and Limnocharis flava (L.) Buchenau growth in acidic contaminated soil supported by microbial inoculants - nguyen, thilam; Song, Shaoxian; Dung, Bui Thi Ngoc; Ahmed, Samreen Riaz; Lahori, Altaf Hussain (Ecological Questions, 2024)
An in situ pot experiment was carried out in a net house to study the combined effect of a mixture of microbial inoculants at different levels of 0, 1, 1.5, 2, 2.5, and 3 g/kg in dry soil with Limnocharis flava (L.) Buchenau plants grown on agricultural land contaminated with lead (Pb) and cadmium (Cd). The results showed that plant growth, fresh inflorescence yields and accumulation of Pb and Cd in L. flava plant parts gradually increased with increasing levels of the applied microbial inoculants in the contaminated soil. The highest total content of Pb and Cd was determined in roots (6.63–32.46 and 0.12–0.72 mg/kg dw), followed by stems and leaves (1.20–3.08 and 0.04–0.09 mg/kg dw) and inflorescence parts (0.012–0.120 and 0.011–0.065 mg/kg fw). The application of microbial inoculants in the range of 2–2.5 g/kg dry soil stimulated the growth and fresh inflorescence yields of L. flava, increased the accumulation of Pb and Cd in inedible parts, ensuring safety for edible parts of L. flava plants in accordance with QCVN8-2:2011/BYT and FAO/WHO regulations. The results of the present work indicate that the flexibility of Pb and Cd can be increased when soil is mixed with microbial inoculants. Long term ex situ experiments are needed to investigate the impact of microbial inoculants mixed with biochar, minerals and nanomaterial for phytomanagement of soil contaminated with multiple metals.